Experimental and theoretical studies on the thermal decomposition of trans-1-chloro-3, 3, 3-trifluoropropene and 2-chloro-3, 3, 3-trifluoropropene and their fire-extinguishing performance. (17th July 2020) - Wu, Rui; Wang, Xingyu; Cheng, Lu; Ren, Changxing; Wei, Xingyou; Zhang, Xiao
Abstract : trans -1-Chloro-3, 3, 3-trifluoropropene and 2-chloro-3, 3, 3-trifluoropropene have the potential to act as fire extinguishing agents, but their thermal decomposition mechanism and fire extinguishing performance have not been investigated. Abstract : trans -1-Chloro-3, 3, 3-trifluoropropene ( trans -CF3 CHCHCl) and 2-chloro-3, 3, 3-trifluoropropene (CF3 CClCH2 ) have the potential to act as fire extinguishing agents, but their thermal decomposition mechanism and fire extinguishing performance have not been investigated. In this paper, thermal decomposition experiments and theoretical calculations were carried out to verify the possible thermal decomposition process and fire extinguishing performance of these potential fire extinguishing agents. trans -CF3 CHCHCl and CF3 CClCH2 can be decomposed into radicals, such as HCl, ˙CF3, and ˙CF2, which can consume ˙OH and ˙H radicals for fire suppression. Furthermore, the experimental and calculation results demonstrated that CF3 CClCH2 shows better thermal stability. To characterize the inhibitory efficiency of trans -CF3 CHCHCl and CF3 CClCH2, the minimum extinguishing concentrations were measured to be 6.8% and 6.9%, respectively. As a result, trans -CF3 CHCHCl and CF3 CClCH2 performed well, and their application as Halon substitutes is worth exploring.